2021
DOI: 10.1016/j.celrep.2021.108946
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 is an essential regulator of brain maturation through regulation of CH methylation

Abstract: Highlights d miR-29 is markedly upregulated during postnatal brain maturation d miR-29 targets Dnmt3a to restrict its expression in vivo in the maturing brain d miR-29 regulates Dnmt3a and mCH to control the expression of synaptic genes d Failure of miR-29 to restrict Dnmt3a leads to neurobehavioral deficits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 91 publications
(108 reference statements)
3
42
1
Order By: Relevance
“…Most studies examining human cortex have found that the level of at least one member of the miR-29 family increases significantly during postnatal development [44,45,47] (but also see [48]). Studies in macaque, pig, rat, and mouse have demonstrated that postnatal miR-29 upregulation with age is highly conserved among mammals [45,49,51,[53][54][55][80][81][82][83]. Notably, Swahari et al [55] examined the levels of miR-29 in mouse cortex at P0-P60 and observed a robust increase in all three family members before the onset of adolescence (P0-P20) and during the transition from early to mid-adolescence (P20-P40).…”
Section: The Mir-29 Family and Mir-132-3p Levels Increase With Age And May Be Dysregulated In Sczmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies examining human cortex have found that the level of at least one member of the miR-29 family increases significantly during postnatal development [44,45,47] (but also see [48]). Studies in macaque, pig, rat, and mouse have demonstrated that postnatal miR-29 upregulation with age is highly conserved among mammals [45,49,51,[53][54][55][80][81][82][83]. Notably, Swahari et al [55] examined the levels of miR-29 in mouse cortex at P0-P60 and observed a robust increase in all three family members before the onset of adolescence (P0-P20) and during the transition from early to mid-adolescence (P20-P40).…”
Section: The Mir-29 Family and Mir-132-3p Levels Increase With Age And May Be Dysregulated In Sczmentioning
confidence: 99%
“…Studies in macaque, pig, rat, and mouse have demonstrated that postnatal miR-29 upregulation with age is highly conserved among mammals [45,49,51,[53][54][55][80][81][82][83]. Notably, Swahari et al [55] examined the levels of miR-29 in mouse cortex at P0-P60 and observed a robust increase in all three family members before the onset of adolescence (P0-P20) and during the transition from early to mid-adolescence (P20-P40). Napoli et al [83] also observed a robust increase of miR-29a-3p in mouse visual cortex prior to adolescence (P10-P25) and throughout adolescence (P25-P60) [83].…”
Section: The Mir-29 Family and Mir-132-3p Levels Increase With Age And May Be Dysregulated In Sczmentioning
confidence: 99%
See 3 more Smart Citations